A Systematic Review of Spiritual and Cultural-Based Digital Interventions for Suicide Risk Prevention among Students - Lenny Aprilianty; Heni Dwi Windarwati; Lilik Supriati (Universitas Muhammadiyah Surakarta, 2026)
Suicide is a major global public health concern and the third leading cause of death among individuals aged 15–29. College students are particularly at risk, and while spiritual and cultural digital interventions exist, they are often implemented separately. This systematic review investigates the effectiveness of integrated spiritual and cultural digital approaches in reducing suicide risk among college students. Following PRISMA guidelines, English-language literature published between 2020 and 2025 was sourced from ScienceDirect, Springer, EBSCO, and Sage using targeted keywords. From 9,272 initial records, 20 studies met the inclusion criteria. The findings reveal that integrated spiritual and cultural digital interventions significantly reduce symptoms of stress, depression, anxiety, and suicidal ideation, while enhancing psychological well-being. Spirituality serves as a protective factor by fostering emotional resilience, hope, and a sense of meaning in life. Cultural relevance such as community values, social solidarity, and family roles is essential in designing effective interventions. Notably, 75% of the reviewed studies reported statistically significant improvements (p<0.05). Digital interventions that integrate spirituality and culture not only improve access to mental health support but also strengthen emotional resilience and life meaning, offering a promising strategy for suicide prevention among college students.